2020
DOI: 10.1017/s0952675720000202
|View full text |Cite
|
Sign up to set email alerts
|

A wug-shaped curve in sound symbolism: the case of Japanese Pokémon names

Abstract: An experiment showed that Japanese speakers’ judgement of Pokémons’ evolution status on the basis of nonce names is affected both by mora count and by the presence of a voiced obstruent. The effects of mora count are a case of counting cumulativity, and the interaction between the two factors a case of ganging-up cumulativity. Together, the patterns result in what Hayes (2020) calls ‘wug-shaped curves’, a quantitative signature predicted by MaxEnt. I show in this paper that the experimental results can indeed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 79 publications
(185 reference statements)
1
12
0
Order By: Relevance
“…Experiment 2 demonstrated that counting and ganging-up cumulativity simultaneously obtain in the domain of sound symbolism (Kawahara, 2020d;Kawahara, Suzuki, & Kumagai, 2020), paralleling recent findings from other areas of probabilistic phonological patterns (Breiss, 2020;Hayes, 2020;McPherson & Hayes, 2016;Zuraw & Hayes, 2017).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Experiment 2 demonstrated that counting and ganging-up cumulativity simultaneously obtain in the domain of sound symbolism (Kawahara, 2020d;Kawahara, Suzuki, & Kumagai, 2020), paralleling recent findings from other areas of probabilistic phonological patterns (Breiss, 2020;Hayes, 2020;McPherson & Hayes, 2016;Zuraw & Hayes, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…Recent experiments by Kawahara and Kumagai (in press) build upon these observations and show that two voiced obstruents evoke stronger sound symbolic images than one voiced obstruent in Japanese. Kawahara (2020d) studied how name lengths, measured in terms of mora counts, affect the judgment of Pokémons evolvedness (see Section 1.4 below for further details) and showed that each mora count increased the probability of nonce names being judged as evolved Pokémon characters. Kawahara, Suzuki, and Kumagai (2020) demonstrated a similar effect of mora counts on judged attack values in Pokémon move names.…”
Section: Previous Studies and The Current Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alderete and Kochetov (2017) andKawahara (2020b) adduce additional reasons why studying sound symbolism can be interesting and important for formal phonologists.4 One related question which I do not delve into in this paper due to space limitation is the issue of universality of sound symbolism. To the extent that sound symbolism is grounded in phonetic properties, and to the extent that speakers of different languages share the same articulators and communicate under comparable physical settings, it would not be surprising if sound symbolic associations are observed universally across languages.…”
mentioning
confidence: 99%